Clinical Study Concerning Adhesive Fixed Partial Prosthesis - Zaharia Agripina; Stefanescu Corina; Davidescu Carolina; Murineanu Rodica (Romanian Society of Oral Rehabilitation, 2009)
The purpose of this clinical study is to prove that prosthetic treatment by adhesive type fixed partial prosthesis still represents an available choice. Material and method: The clinical cases have been selected from the Ovidius University of Constanta, Faculty of Dentistry's Prosthetic Clinic. Patients, all male of gender, having different ages and jobs, have been examined both clinical and paraclinical; a diagnose has been established - single tooth maxillary front edentation (IIIrd Kennedy class) and the treatment plan has been conceived for which the patients agreed in writing. The solution chosen was the manufacture of metal-ceramic Adhesive type fixed partial prosthesis. All the stages were passed through according to standard protocols.Results: Three metal-ceramic Adhesive type fixed partial prosthesis were obtained that successfully restored the morpho-functional capability of the dentomaxilary system. Discussions: The treatment's success factors for the Adhesive type fixed partial prosthesis are: proper selection of the clinical case, the tooth preparation's design, designing the metal frame, prosthesis adaptation and cementing. Conclusions: In the case of a single tooth anterior edentation, the Adhesive type fixed partial prosthesis represents a currently used treatment solution, because it is conservative, aesthetical, periodontal prophylactic and can be successfully applied both as a temporary prosthesis and also and a permanent one.